Prevalence of Mycoplasma Penetrans in Urethral and Rectal Specimens from Men Attending an STI Clinic - Mie Gesine Laake; Axel Skafte-Holm; Thomas Roland Pedersen; Jørgen Skov Jensen; Kirsten Salado-Rasmussen (Acta Dermato-Venereologica)
Mycoplasma penetrans has gained attention in relation to non-gonococcal urethritis (NGU), a syndrome where a significant proportion of patients have no identified aetiological agent. In this study, we estimated the prevalence of urethral and rectal M. penetrans in a male population attending a sexually transmitted infection (STI) clinic in Copenhagen, Denmark. Specimens were assessed using M. penetrans-specific real-time polymerase chain reaction (PCR). Demographic characteristics and clinical symptoms were extracted from patient records. A total of 704 urethral specimens and 223 rectal specimens from 721 individual male patients were included. The prevalence of urethral and rectal M. penetrans was 0.3% and 2.7%, respectively. Overall, the prevalence among men who have sex with men (MSM) was 3.6%, significantly higher than in men who have sex with women (p < 0.001). Among MSM, a higher number of partners was associated with M. penetrans infection (p = 0.008). No association was found between the presence of M. penetrans and clinical symptom status, and its pathogenic potential remains unclear.